Kepatuhan Minum Obat Antidiabetika Oral Pasien Ulkus Diabetikum Rawat Jalan di Klinik X Pontianak Menggunakan Metode Kualitatif MMAS-8 - Yunike Dwi Larasati; Nurmainah Nurmainah; Ressi Susanti (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Compliance is a major factor in determining the success of treatment. Non-compliance with taking medication in patients with diabetes mellitus has an impact on the risk of complications, one of which is diabetic ulcers. Diabetic ulcers are chronic wounds that occur due to hyperglycemia and abnormal blood circulation, which causes an increase in blood sugar levels. This study aims to analyze the level of adherence to taking oral antidiabetic drugs and the factors that influence adherence to taking antidiabetic drugs in outpatient diabetic ulcer patients at X Clinic, Pontianak. This research is a type of cross-sectional research, the sampling technique is purposive sampling. The number of samples that met the inclusion and exclusion criteria was 100 patients. Data was collected by filling out a questionnaire. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. The results showed that the characteristics of patients who visited the X Clinic Pontianak tended to be 45 years old (85%), female (67%), patients with 5 years of illness (55%), patients with a single type of treatment ( 68%), patients taking metformin (47%), and only 27% of patients adhering to oral antidiabetic drugs. Chi-square analysis showed that there was no significant relationship between age (p=1,000), gender (p=0,966), length of stay (p=0,946), type of treatment (p=0,202) on patient compliance in using antidiabetic drugs. From this study, it can be concluded that age, gender, length of suffering, and type of treatment do not affect adherence to taking oral antidiabetic drugs in diabetic ulcer patients.